PRONUNCIBOT: TELEGRAM PRONUNCIATION DICTIONARY FOR EFL LEARNERS - Ana Ahsana El Sulukiyyah; Dewi Masitho Istiqomah (ETERNAL (English, Teaching, Learning and Research Journal), 2022)
Learning English pronunciation is sometimes confusing because of its irregular forms. What we see in the written form is not the same as how it is pronounced. This study is aimed to develop the online pronunciation dictionary for EFL learners that can be accessed easily using Telegram feature named Telegram bot. The pronunciation dictionary developed here named Pronuncibot. It is a research and development (R&D) method with some custom procedure from Gall, Borg & Gall those are pre-research, research planning, media developing, expert validation, revising, try out, test and final design. The subject of the study was the English Education Study Program students. The results showed that in the process of the development of Pronuncibot, there were some revisions need to accomplish this bot, one of them was completing the two major accents. For the field testing, it was shown that there were some improvements from students’ pronunciation before and after using Pronuncibot. It can be shown in pronouncing some available words and menus like past verbs, animals and homophones. Furthermore, from questionnaire results, it was shown that students were agree that the use of Pronuncibot can assist their pronunciation practice. In conclusion, the development of this bot can provide students’ learning flexibility as the hope of digital learning goal